Kiai's Leadership Role In Developing The Character Of Students - Abdur Rahman (JOSSE: Journal of Social Science and Economics, 2022)
The influence of modernization that has an impact on all aspects of life. Many future generations are off track because they cannot face life's problems. Does not look at someone who has a religious background (santri) or not. Moreover, if students (santri) who have bad personalities, are naughty and unruly without being developed/formed good characters will definitely have a negative impact in the life to come. Therefore, it is necessary to develop a good and strong character so that the next generation of this nation can face the problems that will be faced in the life to come. This is where the role of the leader is needed in developing his special character in educational institutions (pesantren). This study aims to (1) describe the character of the santri in the Darul Ihsan Menganti Gresik Islamic boarding school, (2) describe and analyze the Kiai leadership style at the Darul Ihsan Menganti Gresik Islamic boarding school, (3) describe and analyze the leadership role of the kiai in developing the character of the santri in the Islamic boarding school. Darul Ihsan Menganti Islamic Boarding School. This research method uses a qualitative descriptive approach, this type of research is a case study. The location of this research is Darul Ihsan Menganti Islamic Boarding School, Gresik. The method of data collection using interviews, observation, and documentation. The data analysis technique in this study used a data collection model, data reduction, data presentation, and drawing conclusions. From the results of this study it was found that: (1) The character of the santri in the Darul Ihsan Islamic boarding school strongly encourages the formation of character, as well as good morals and character, the dominating character that is developed is responsibility, honesty, discipline, independence (2) The leadership style that is developed implemented at the Darul Ihsan Menganti Islamic Boarding School, Menganti Gresik is a democratic leadership style. In decision making, take a consensus deliberation system. The social relationship between Drs. KH. Mulyadi, MM as the leader with the Asatidz board of his subordinates are like friends, easy to get along and there is no dividing distance between the two. While the relationship between Drs. KH. Mulyadi, MM and their students are likened to the relationship between parents and their children. (3) The role of Drs. KH. Mulyadi, MM in the context of forming and developing the character of students, namely as caregivers, advisors, educators (educators) and motivators (motivators), figures and role models, facilitators and coordinators. The role of Drs. KH. Mulyadi, MM the most important thing in developing the character of students is as an educator (educator) and a figure and role model.